High level of protection against COVID-19 after two doses of BNT162b2 vaccine in the working age population – first results from a cohort study in Southern Sweden. Issue 2 (1st February 2022) - Björk, Jonas; Inghammar, Malin; Moghaddassi, Mahnaz; Rasmussen, Magnus; Malmqvist, Ulf; Kahn, Fredrik
Abstract: Background: Vaccine effectiveness against COVID-19 needs to be assessed in diverse real-world population settings. Methods: A cohort study of 805, 741 residents in Skåne county, Southern Sweden, aged 18–64 years, of whom 26, 587 received at least one dose of the BNT162b2 vaccine. Incidence rates of COVID-19 were estimated in sex- and age-adjusted analysis and stratified in two-week periods with substantial community spread of the disease. Results: The estimated vaccine effectiveness in preventing infection ≥7 days after second dose was 86% (95% CI 72–94%) but only 42% (95% CI 14–63%) ≥14 days after a single dose. No difference in vaccine effectiveness was observed between females and males. Having a prior positive test was associated with 91% (95% CI 85–94%) effectiveness against new infection among the unvaccinated. Conclusion: A satisfactory effectiveness of BNT162b2 after the second dose was suggested, but with possibly substantially lower effect before the second dose.